The development of early social cognitive skills in neurogenetic syndromes associated with autism: Cornelia de Lange, fragile X and Rubinstein–Taybi syndromes - Katherine Ellis (BMC, 2021)
Abstract Background Cornelia de Lange (CdLS), Fragile X (FXS) and Rubinstein–Taybi syndromes (RTS) evidence unique profiles of autistic characteristics. To delineate these profiles further, the development of early social cognitive abilities in children with CdLS, FXS and RTS was compared to that observed in typically developing (TD) and autistic (AUT) children. Methods Children with CdLS (N = 22), FXS (N = 19) and RTS (N = 18), completed the Early Social Cognition Scale (ESCogS). Extant data from AUT (N = 19) and TD (N = 86) children were used for comparison. Results Similar to AUT children, children with CdLS, FXS and RTS showed an overall delay in passing ESCogS tasks. Children with CdLS showed a similar degree of delay to AUT children and greater delay than children with FXS and RTS. The CdLS, FXS and RTS groups did not pass tasks in the same sequence observed in TD and AUT children. Children with CdLS (p = 0.04), FXS (p = 0.02) and RTS (p = 0.04) performed better on tasks requiring understanding simple intentions in others significantly more than tasks requiring joint attention skills. Conclusions An underlying mechanism other than general cognitive delay may be disrupting early social cognitive development in children with CdLS, FXS and RTS. Factors that may disrupt early social cognitive development within these syndromes are discussed.